Konsep Salvation Menurut Agama Kristian: Satu Huraian Awal - Mohd Hambali @ Khambali, Khadijah (Jurnal Usuluddin, 1999)
The Christianity especially the Catholic Church believes that the relationship between God and human beings was greatly affected bythe Fall. The very roots of human nature were damaged by the sin of the first parents i.e. Adam and Eve. Left to the own devices, the man is helpless. Catholic believes, however, that they have been saved from the consequences of sin by the death of Jesus on calvary and by his resurrection from the dead. God’s forgiveness is now freely available to all those who believe in Christ. Those who respond to this offer of salvation are the "redeemed" - those "bought back" from the slavery of sin. To know more about that topic, this article tries to emphasize the concept of the salvation in Christianity especially in Catholic Church’s belief.